The Effect of Source Credibility and Argument Quality in Smartphone Reviews on YouTube Towards Purchase Intention - Margaretha Pink Berlianto (Indonesian Marketing Journal, 2026)
This study aims to investigate the influence of argument quality and source credibility on attitude, e-wom adoption, and purchase intention, and to evaluate the influence of attitude and e-WOM on purchase intention in the smartphone industry. The population of this study consists of individuals residing in Jakarta who have watched smartphone reviews on YouTube. This study employed a non-probability sampling technique using purposive sampling. A total of 250 respondents were included, and SmartPLS 4 was used to analyze the data. The results of this study indicate that argument quality does not influence attitude; that argument quality and source credibility have a positive influence on e-WOM adoption; that argument quality, attitude, and e-WOM adoption have a positive influence on purchase intention; and that source credibility does not influence purchase intention. The theoretical implications of this study are that it successfully confirms the Information Adoption Model, and TRA. The managerial implications of this study are as follows: smartphone industry players need to improve the quality of arguments, the credibility of sources, attitude, and e-WOM adoption, as these factors influence purchase intention.